Tindak Pidana Kekerasan Seksual Pada Anak di Kota Jambi Dalam Analisis Perlindungan Hukum - Hartono, M Rudi; Aditama, Ryan; Sucipto, Ahmat (Universitas Batanghari Jambi, 2024)
Legal protection is an activity to protect individuals by harmonising the relationship of values or rules that manifest in attitudes and actions in creating order in the association of life between fellow human beings. Basically, the existence of criminal law serves to regulate matters relating to criminal offences or crimes, one of which is the crime of sexual violence. One of the most vulnerable parties to sexual violence is minors who are still under the age of 18. Forms of sexual violence that often occur in children are generally in the form of sexual abuse, making physical contact by holding and touching the sexual parts of children, having intimate relationships with children, sex trafficking, showing pornographic films to children, and masturbating in front of children. This study aims to obtain a more in-depth description of the legal protection for child victims of sexual violence in Jambi City, the obstacles found in legal protection for child victims of sexual violence and the efforts made to overcome the obstacles found. The method used in this research is empirical research method, while the approach used in this research is socio legal research. The data collection method in this study uses data sources in the form of field data sources and library data sources. The conclusion in this study is that legal protection for child victims of sexual violence in Jambi City is carried out preventively and also repressively. The obstacles found in legal protection for child victims of sexual violence in Jambi City are the lack of public understanding of the importance of legal protection for children who are victims of sexual violence, as well as the lack of evidence in handling the case. Efforts made to overcome the obstacles found are to provide socialisation in private to increase public understanding of the importance of legal protection